Evaluation of Teachers’ Performance and School Environment on the Implementation of the Merdeka Curriculum: A Literature Review - Hastuti, Meiliza; Agustina, Eka (PPSDP International Journal of Education, 2025)
This study evaluates the role of teacher performance and school environmental support in the implementation of the Merdeka Curriculum in Indonesia. Teachers’ performance, including pedagogical skills, innovation in teaching, and project-based learning management, as well as school environmental support in the form of technological facilities, a conducive work climate, and a collaborative culture, are two main factors in the success of this curriculum. Through a systematic literature review, the findings of this study indicate that adequate facilities and managerial support contribute significantly to teacher motivation and performance effectiveness, which have a positive impact on the implementation of the Merdeka Curriculum. However, obstacles such as high administrative burdens, unequal access to training, and lack of managerial support still hinder the optimization of teachers’ performance. This study found that the synergy between adequate teacher competence and optimal environmental support can create a more interactive and independent learning experience for students. Thus, the conclusion of this study emphasizes the need for policies that support reducing administrative burdens, increasing access to ongoing training, and providing adequate facilities. These findings are expected to be the basis for developing education policies that are more responsive to the needs of teachers and schools in order to strengthen the implementation of the Merdeka Curriculum in Indonesia.